2016
DOI: 10.3390/ijms17081165
|View full text |Cite
|
Sign up to set email alerts
|

A Female-Biased Odorant Receptor from Apolygus lucorum (Meyer-Dür) Tuned to Some Plant Odors

Abstract: Apolygus lucorum (Meyer-Dür) (Hemiptera: Miridae) is a serious pest of cotton, jujube, grape and many other crops around the world. Understanding how olfactory information directs this insect to its host plants may provide environment-friendly approaches to the control of its population in agriculture. In our study, we cloned an odorant receptor gene, AlucOR46, that was specifically expressed in antennae and female-biased. Functional expression of AlucOR46 in Xenopus oocytes showed that it is tuned to six plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…AlucOR46, a female‐biased OR in A. lucorum , tuned to six plant volatiles namely ( S )‐(−)‐Limonene, ( R )‐(+)‐Limonene, ( E )‐2‐Hexenal, ( E )‐3‐Hexenol, 1‐Heptanol and (1 R )‐(−)‐Myrtenol. These results suggest that this receptor could be involved in finding the appropriate host plants for feeding and oviposition . However, another male‐biased receptor in A. lucorum , AlucOR40, only responded to one ligand in Xenopus heterologous expression system, suggesting that the AlucOR40 might be involved in detection of ( E )‐2‐hexenol and play a role in identification of female by male during mating .…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…AlucOR46, a female‐biased OR in A. lucorum , tuned to six plant volatiles namely ( S )‐(−)‐Limonene, ( R )‐(+)‐Limonene, ( E )‐2‐Hexenal, ( E )‐3‐Hexenol, 1‐Heptanol and (1 R )‐(−)‐Myrtenol. These results suggest that this receptor could be involved in finding the appropriate host plants for feeding and oviposition . However, another male‐biased receptor in A. lucorum , AlucOR40, only responded to one ligand in Xenopus heterologous expression system, suggesting that the AlucOR40 might be involved in detection of ( E )‐2‐hexenol and play a role in identification of female by male during mating .…”
Section: Discussioncontrasting
confidence: 52%
“…Among a large number of ORs expressed in the antennae of A. lucorum , a few have been functionally characterized and their ligands have been identified . AlucOR46, a female‐biased OR in A. lucorum , tuned to six plant volatiles namely ( S )‐(−)‐Limonene, ( R )‐(+)‐Limonene, ( E )‐2‐Hexenal, ( E )‐3‐Hexenol, 1‐Heptanol and (1 R )‐(−)‐Myrtenol.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our tissue expression profiles suggest that AlinOBP6 is strongly expressed in adult antenna tissue and is female‐biased (Fig. ), indicating a potential olfactory role in adult A. lineolatus in perceiving female‐related chemical cues for feeding and oviposition (Anderson et al ., ; Zhang et al ., ). The results from the ligand binding assay showed that AlinOBP6 specifically binds to the tested host plant volatiles rather than the bug‐produced sex pheromones, with high binding affinity [dissociation constant (Ki) below 10 µM] to 6‐methyl‐5‐hepten‐2‐one, acetophenone, nonanal and five host plant terpenoids (Fig.…”
Section: Discussionmentioning
confidence: 97%